Parametric Study of Resistive Plasmoid Instability - Lotfi, Hossein; Hosseinpour, Mahboub (Frontiers in Astronomy and Space Sciences, 2021)
By using 2.5-dimensional resistive MHD simulations, dynamics of the plasmoid instability in a Harris current sheet has been studied with taking into account two main controlling parameters: the plasma-β in the range (0 < β < 1) and the amplitude ratio of magnetic guide field to the reconnection plane field in three different cases with zero, uniform, and non-uniform guide field. Varying the plasma-β changes the plasma compressibility which affects significantly on the linear and nonlinear growth rates of the plasmoid instability. For each of three cases, some associated scaling relations between the instability growth rate, the plasma-β and the magnitude of guide field are obtained.